The Effect of Zakat, Infaq, and Shodaqoh Distribution on the Poverty Level in Indonesia - Izzul Mustasyfa Hamid; Muhammad Wildan Khoirul Azka (Yayasan Azhar Amanaa Yogyakarta, 2026)
Poverty remains a global issue and a significant challenge in Indonesia. Although the national poverty rate has declined over time, its potential remains high, especially in rural areas and the eastern regions of Indonesia. This study aims to analyze the effect of Zakat, Infaq, and Shodaqoh (ZIS) distribution on poverty levels in Indonesia. Using an associative quantitative approach with time-series data from 2002–2023 obtained from BAZNAS and BPS, along with multiple regression analysis, this study tests the hypotheses both partially and simultaneously. The results show that zakat distribution has a negative and significant effect on poverty levels. In contrast, infaq and shodaqoh distribution have a positive and significant effect on poverty levels. Simultaneously, the distribution of zakat, infaq, and shodaqoh (ZIS) has a significant effect on poverty levels in Indonesia, contributing 87.58% in explaining the variation of poverty levels. These findings indicate that ZIS has great potential as a structural instrument for poverty alleviation in Indonesia, provided that it is managed effectively and in a well-targeted manner.